2022
DOI: 10.1073/pnas.2121671119
|View full text |Cite
|
Sign up to set email alerts
|

Auxin regulates source-sink carbohydrate partitioning and reproductive organ development in rice

Abstract: Carbohydrate partitioning between the source and sink tissues plays an important role in regulating plant growth and development. However, the molecular mechanisms regulating this process remain poorly understood. In this study, we show that elevated auxin levels in the rice dao mutant cause increased accumulation of sucrose in the photosynthetic leaves but reduced sucrose content in the reproductive organs (particularly in the lodicules, anthers, and ovaries), leading to closed spikele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…A previous study suggested that auxin might regulate sucrose phloem unloading during rice seed development (Deng et al., 2021). Another recent study further demonstrated that the rice auxin signaling components OsARF2 and OsARF18 directly regulate the expression of the sucrose transporter OsSUT1 to organize sucrose transport and reproductive organ development (Zhao et al., 2022). Auxin also has been found to control anther dehiscence timing by regulating anther endothecium lignification (Cecchetti et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that auxin might regulate sucrose phloem unloading during rice seed development (Deng et al., 2021). Another recent study further demonstrated that the rice auxin signaling components OsARF2 and OsARF18 directly regulate the expression of the sucrose transporter OsSUT1 to organize sucrose transport and reproductive organ development (Zhao et al., 2022). Auxin also has been found to control anther dehiscence timing by regulating anther endothecium lignification (Cecchetti et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome analysis plays an important role in the study of rice molecular mechanisms [ 45 , 46 ]. For example, RNA-Seq sequencing detected a significant down-regulation of OsSUT1 expression in dao mutants and further verified that OsSUT1 can directly regulate the source-sink allocation of sucrose in plants [ 47 ]. Transcriptome data analysis also revealed that OsNCED3 mainly regulates rice dormancy through hormone and signal transduction [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of tomato SlARF4 enhances sugar accumulation in fruit, implying a connection between sugar partitioning and auxin signaling (Sagar et al 2013). Zhao et al recently found that rice dao mutant, which failed to convert IAA into OxIAA, had defects in sugar partition between source (leaf) to sink (spikelet) tissue (Zhao et al 2022c). dao mutant upregulates auxin signaling component OsARF18 but downregulates OsARF2.…”
Section: Seed Quality and Yieldmentioning
confidence: 99%
“…Strikingly, the cis-element motif of SuREs (GTCTC) shows high sequence similarity with auxin-responsive elements (AuxREs: TGTCTC), implying a synergistic or antagonistic regulation between auxin and sugar on transcriptional level. OsARF18 acts as a repressor of OsARF2-OsSUT1 complex, feedback regulates sugar transport through auxin signaling (Zhao et al 2022c). Hence, auxin signaling cascade is also involved in carbohydrate partitioning, providing an important implication for raising seed quality.…”
Section: Seed Quality and Yieldmentioning
confidence: 99%